PENGARUH PENGGUNAAN BUKU AJAR ELEKTRONIK DALAM MODEL PEMBELAJARAN LANGSUNG TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 1 LUBUK ALUNG - Soraya Anori (PILLAR OF PHYSICS EDUCATION, 2013)
Abstract — The aim of research is to investigate effect of using physics learning book in direct instruction model to the learning outcomes of students grade X SMAN 1 Lubuk Alung. Type of research is Quasi Experiment Research. As population in research is all students grade X SMAN 1 Lubuk Alung in academic year 2012/2013. The sampling technique which used was purposive sampling technique. The research sample is X1 consisting of 30 students and X2 consisting of 30 students. Data collection techniques are written test for the cognitive domain and observation for affective domain. Technique of data analysis is hypothesis testing by compare mean test on real level 0.05. Results of research showed that learning outcomes of students by using physics learning book in direct instruction model on cognitive and affective respectively 76.50 and 78.77. The use physics learning book in direct instruction model give better learning outcomes of student than didn’t use the physics learning book in direct instruction model.   Keywords — physics learning book, direct instruction model, learning outcomes, cognitive, affective